Lepromatous leprosy with a suspected 30-year incubation period: A case report of a practically eradicated area. Issue 4 (August 2022) - Jariyakulwong, Niporn; Julanon, Narachai; Saengboonmee, Charupong
الملخص : أهداف البحث: يهدف هذا التقرير إلى توضيح وتذكير مقدمي الرعاية الصحية بأنه على الرغم من اعتباره قد تم استئصال الجذام في منطقة معينة، إلا أنه يمكن العثور على الإصابة به نتيجة فترة حضانة طويلة بشكل غير عادي. طرق البحث: أبلغنا عن حالة من الجذام لأنثى تايلندية تبلغ من العمر 48 عاما ظهرت عليها أعراض جلدية وعصبية كلاسيكية. تم إجراء الفحوصات الجسدية وإعداد اللطاخة الفلعية مع التلوين الصامد للحمض للوفاء بالمعايير التشخيصية لمنظمة الصحة العالمية. تم وصف الأنظمة العلاجية بناء على توصية منظمة الصحة العالمية. النتائج: تم تشخيص إصابة المريضة بالجذام بالنظر إلى استيفاء جميع العناصر الأساسية لمعايير التشخيص لمنظمة الصحة العالمية؛ الفحوصات الجسدية والميكروسكوبية. تقابل الآفات الجلدية عن طريق الفحص البدني نوع جذامي. أظهر تحضير اللطاخة الفلعية من الآفات وجود عصيات وفيرة صامدة للأحماض. كانت المريضة تعيش فقط في منطقة تم فيها استئصال الجذام عمليا ولم يتم الإبلاغ فيها عن حالات جديدة. وبالتالي، فإن أكثر عوامل الخطر المريبة لإصابتها هو الاتصال الوثيق قبل 30 عاما مع أحد أفراد عائلتها المصاب بالجذام في نفس المنزل لمدة أسبوع. الاستنتاجات: يوضح هذا التقرير حالة نادرة من الجذام مع فترة حضانة طويلة في منطقة غير موبوءة. تم الإبلاغ عن مثل هذه الحضانة الطويلة بشكل غير عادي فقط للقرود غير البشرية، ولكنها نادرة للغاية بالنسبة للبشر. تذكر هذه المعلومات مقدمي الرعاية الصحية بأن الجذام ليس مرضا في الماضي، ولا يزال برنامج المراقبة الدقيقة للجذام ضروريا حتى في المنطقة التي تم استئصالها منها. Abstract: Objectives: This report aims to demonstrate and remind healthcare providers that, despite being considered eradicated in a specific area, leprosy can still be found due to its unusually long incubation period. Methods: A case of leprosy has been reported in a 48-year-old Thai woman who presented classic dermatological and neurological symptoms. A physical examination and slit smear preparation with acid-fast staining was performed to fulfil the diagnostic criteria of the World Health Organization (WHO). Therapeutic regimens were prescribed according to WHO recommendations. Results: A patient was diagnosed with leprosy given that all cardinal signs of WHO diagnostic criteria were met after both physical and microscopic examinations. Physical examination of the skin lesions revealed the lepromatous type. Slit smear preparation of the lesions revealed abundant acid-fast bacilli. The patient has been living solely in an area where leprosy has been practically eradicated, with no new cases reported. The most likely cause of her infection is her close contact with a leprosy-infected family member 30 years ago, with whom she shared a house for a week. Conclusions: This report describes a rare case of leprosy with a long incubation period in a non-endemic area. Only non-human primates have had such an unusually long incubation period, which is extremely rare in humans. This information reminds healthcare providers that leprosy is not a disease of the past, and a careful surveillance program for leprosy remains necessary, even in eradicated areas.